Introduction - Evans, John Harry (The Accounting Review, 2014)
It is well recognized that a critical step in the development of modern accounting research was the landmark study in 1968 by Ray Ball and Phil Brown (Ball and Brown 1968). Their study demonstrated the usefulness of accounting by documenting an association between financial statement information and stock prices, a market phenomenon. At about the same time, behavioral accounting researchers began to explore associated questions at the individual level, seeking to determine how accounting information affects individual decisions. Recent research in accounting and finance has drawn on results of behavioral experiments in an attempt to explain market anomalies, as first identified by Ball and Brown themselves (1968, 173).The two studies in this neuroscience forum provide a deeper understanding by again pushing the focus down to the more fundamental or “ultimate” source within an individual's brain. As Greg Waymire notes in his commentary, this approach has the potential to offer new insight into the relation between longstanding accounting principles and fundamental human behaviors reflected in social norms such as reciprocity and fair-dealing. In the process, this work offers accounting researchers new tools for understanding and explaining both individual and market behavior.